Analisis Pendapatan, Biaya Bersumber Underwriting, dan Sumber Investasi Lain pada Perusahaan Asuransi Kerugian - Yohanes Jhony Kurniawan; Heppy Julianto (CV. Ulil Albab Corp, 2024)
This research aims to create a general map of Income, Costs Sourced from Underwriting and Other Investment Sources in Casualty Insurance Companies. So based on the above we will raise the research title